2010
DOI: 10.1161/circep.109.894329
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Inhibitory G-Protein Gα i2 Predisposes to Ventricular Cardiac Arrhythmia

Abstract: Background We have explored the role that inhibitory heterotrimeric G-proteins have in ventricular arrhythmia. Methods and Results We studied mice with global genetic deletion of Gαi2 (Gαi2 (−/−)) and find that they have a prolonged QT interval on the surface ECG when awake and studied with telemetry. We used in-vivo electrophysiology studies and found that the Gαi2 (−/−) mice have a reduced ventricular effective refractory period and a predisposition to ventricular tachycardia when challenged with programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Although the issue has also been addressed by others [19], [20], [33], our study is the first to demonstrate small but significant changes of basal whole-cell current density: a reduction in myocytes from Gα i2 −/− mice and an increase in myocytes from Gα i3 −/− mice. The altered steady-state inactivation and recovery observed with Gα i2 −/− under basal conditions (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although the issue has also been addressed by others [19], [20], [33], our study is the first to demonstrate small but significant changes of basal whole-cell current density: a reduction in myocytes from Gα i2 −/− mice and an increase in myocytes from Gα i3 −/− mice. The altered steady-state inactivation and recovery observed with Gα i2 −/− under basal conditions (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…This likely translates into the more reduced peak in the current voltage plot in our study. Interestingly, Zuberi et al [19] compared Gα i2 −/− mice with Gα i1 −/− /Gα i3 −/− double knockout mice and found distinct effects on surface ECGs: in Gα i2 −/− animals (but not in the double knockout mice), the effective refractory period was reduced and ventricular arrhythmias were induced more easily. In summary, Gα i2 protein deletion showed dramatic consequences on channel regulation in vivo and ex vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo electrophysiological studies using the EPR-800 catheter were carried out as previously described [18]. Atrial burst pacing was found to be the most consistent method for AF induction, and was performed at a rate of 600 bpm (100 ms coupling interval) for 25 s after which pacing was switched off.…”
Section: Methodsmentioning
confidence: 99%
“…Our own previous studies showed an effect on cardiac function in global G α i2 KO mice, though we have ascribed this largely to direct effects on cardiac tissue (Zuberi et al. , ). Other investigators have shown a potential role for G α i2 in the rat in mediating hypertensive responses (Wainford et al.…”
Section: Discussionmentioning
confidence: 86%
“…An octapolar 1.1F cardiac electrophysiology catheter was inserted into the right ventricular apex through the right internal jugular vein to pace the heart as previously described (Zuberi et al. ; Machhada et al. ).…”
Section: Methodsmentioning
confidence: 99%